On one effective difference scheme for the convection‐diffusion problem - Gromyko, G. (Mathematical Modelling and Analysis, 2001)
The given paper is devoted to build‐up of the special economic difference schemes for non‐stationary one and two‐dimensional problems of a convection ‐ diffusion permitting to take into account convective and diffusion terms from the uniform point of view. On the basis of a multicomponent schemes build‐up procedure, bound up with region decomposition of the cells of mesh, the economic multicomponent iterative algorithm is constructed. A series of numerical calculations on some test problems solution including Burgers problem is reduced, and the comparison with known, most spread schemes is proceeded.Konvekcijos – difuzijos uždavinių efektyvios baigtinių skirtumų schemosSantrauka. Darbe pasiūlytas naujo tipo baigtinių skirtumų schemos, aproksimuojančios konvekcijos ir difuzijos procesus. Pateikta bendra metodika, kuri apibendrina eksponentinio tipo schemas. Gerai žinoma, kad tokio tipo schemos atskirais atvejais yra tikslios. Sudaryti ekonomiški schemos realizavimo algoritmai, kuriuose panaudota daugiakomponentinių iteracinių metodu idėja. Pateikti apibendrinimai dvimačiams uždaviniams. Teoriniai rezultatai iliustruojami skaitinio eksperimento rezultatais.First Published Online: 14 Oct 2010